2021
DOI: 10.21037/tau.2020.03.34
|View full text |Cite
|
Sign up to set email alerts
|

Genetic causes and management of male infertility

Abstract: Infertility affects approximately 15% of couples. With infertility such a common problem in a generally healthy age group, complete evaluation is needed of both men and women. Infertility work up for men includes a semen analysis, the results of which suggest various supplemental studies, including karyotype. Karyotype is indicated when a patient has findings on history or physical exam concerning for chromosomal abnormalities, azoospermia, or severe oligospermia (count <5 million/mL). The most common chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
3
1
0
Order By: Relevance
“…Nevertheless, chromosomal deletions, translocations, inversions, and insertions have also been described. 20 Reported karyotypic abnormalities among infertile men is up to 15%, 21 which is in accordance with our findings. In 2017 a case series and literature review of 46, XX patients diagnosed during fertility evaluation reported a total of 55 cases in this setting; thus, with this study, we are adding two more patients to the described ones.…”
Section: Chromosomal Abnormalitiessupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, chromosomal deletions, translocations, inversions, and insertions have also been described. 20 Reported karyotypic abnormalities among infertile men is up to 15%, 21 which is in accordance with our findings. In 2017 a case series and literature review of 46, XX patients diagnosed during fertility evaluation reported a total of 55 cases in this setting; thus, with this study, we are adding two more patients to the described ones.…”
Section: Chromosomal Abnormalitiessupporting
confidence: 92%
“…An OAT was the initial diagnosis, and a shared decision for sperm donation was chosen by the couple due to the low probability of pregnancy after ART and concerns about offspring transmission risks. The absence of a previous diagnosis of all our patients but one Klinefelter patient is consistent with the literature, which reports a low awareness of this condition and a misconception that all these patients have the classical phenotype of gynecomastia, hypogonadism, a tall stature, and limited facial and body hair, 19,20 whilst currently it is well established that it can present with a highly variable phenotype. According to literature, findings of serum testosterone inferior to the normal limit can range from 65 to 85% of adult patients with Klinefelter syndrome.…”
Section: Chromosomal Abnormalitiessupporting
confidence: 90%
See 1 more Smart Citation
“…Human infertility may have a hereditary component, although the precise defects implicated and the genetic process by which they are transmitted remain unclear [ 6 , 7 ]. The present report aimed to present three cases of male patients who consulted the genetic unit because of infertility problems.…”
Section: Discussionmentioning
confidence: 99%